Exploring Senior High School EFL Teachers’ Beliefs Regarding Learner Autonomy - Wirapatni, Anak Agung Istri Sri; Nitiasih, P. K.; Artini, L. P. (Journal of Education Reseach and Evaluation, 2021)
Since Indonesian education paradigm shifted from teaching to learning, the development of learner autonomy is more emphasized on the learner-centeredness. Henceforth, it is important to conduct a study of teachers’ beliefs regarding learner autonomy as it is widely known that teachers are recognized as an active agent to inculcate autonomy among learners. This study aims to explore EFL teachers’ beliefs regarding the idea of learner autonomy and its development within senior high school settings. This study was a mixed method study that employed a questionnaire and interview as instruments to obtain the data. The participants of this study were 18 senior high school EFL teachers. The result of the study shows that teachers hold very positive beliefs toward learner autonomy. Most of the teachers believe their learners are less autonomous in learning. Learners tend to be passive and less independent of teacher. Teachers assert that they are already promoting learner autonomy within their teaching. Some efforts have been done by EFL teachers to promote autonomy among learners such as giving freedom for learners to express themselves in learning, giving learners opportunities to solve their problems as well as motivating the learners to learn English. The constraints that teachers encounter basically derived from two factors: intrinsically from the learners’ low motivation to learn and extrinsically from the school facilities that are less adequate to support the development of learner autonomy.